(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This article describes the role of English, which is widely used in the world, in our country, the current problems of its introduction into the education system and ways to solve them.